Phosphate Level in Some Selected Surface and Ground Water Bodies of Rajshahi City Corporation (Journal of Environmental Science and Natural Resources, 2015)
Optimum PO4-P level in surface and ground water is essential for maintaining good health and environment. In this study, the PO4-P level was measured for 148 different water samples collected from ponds, supply tape and tube-well of 8 different areas of Rajshahi City Corporation. All the sites of surface water bodies crossed the United States Environmental Protection Agency (USEPA) criterion of 0.01-0.03 mg L-1 PO4P to be free from eutrophication. Among the samples, 4.2% were within the range (0.025-0.1 mg L-1) of onset of eutrophication while 95.8% crossed the hyper-eutrophication level (> 0.10 mg L-1). However, most of the ground (83.1%) and tap (92.7%) water were excellent in quality for drinking with respect to PO4P level (